Perumusan Kebijakan: Pengaruh Disiplin dan Lingkungan terhadap Kinerja dan Kepuasan Kerja - Samsuri; Roestamy, Martin; Warizal; Rusli, Radif Khotamir (JURNAL ILMIAH GEMA PERENCANA, 2025)
This research provides a policy-focused analysis of how organizational discipline and work environment policies influence employee performance through job satisfaction, grounded in the Indonesian legal framework. Using path analysis on data from 94 employees at PT. Catur Dakwah Crane Farmasi Bogor, this study evaluates the on-the-ground implementation of national labor regulations, specifically Law Number 13 of 2003 concerning Manpower. This rigorous methodological approach—utilizing probability sampling, validated psychometric instruments, and path analysis via SPSS—was strategically employed to empirically deconstruct and verify the posited theoretical framework, thereby ensuring the findings' robustness for informing evidence-based policy. The empirical findings reveal a dual-pathway mechanism to performance: an affective pathway mediated by job satisfaction (particularly for work environment policies) and a procedural pathway operating directly through discipline. Results demonstrate that: 1) work discipline and work environment have direct positive and significant effects on job satisfaction (R² = 0.512); 2) work discipline, work environment, and job satisfaction all have direct positive and significant effects on employee performance (R² = 0.635); 3) job satisfaction does not mediate the discipline-performance relationship, indicating a strong situation effect; and 4) job satisfaction significantly mediates the environment-performance relationship. These findings provide evidence-based recommendations for both national labor policy formulation and organizational-level policy implementation in the Indonesian pharmaceutical sector.